Geological journey through the Himalaya - Early research and discoveries (Journal of Nepal Geological Society, 2023)
A number of contributions to the understanding of geology of Himalaya prior to the 20th C. are described. These include observations made by the Chinese about marine fossils found in high mountains; records from 1720s of the Jesuit Priest, Ippolito Desideri, along the course of the Yarlung-Tsangpo-Brahmaputra River; the work of Cautley and Falconer on vertebrate fossils from Miocene of the Siwaliks; and the first geological traverse of the mountain chain. This latter was undertaken by Lieutenant Richard Strachey in 1848 and his detailed cross sections were published in 1851. It is this transect that represents the ‘journey’ described in this paper where Strachey’s observations on the geology of the Himalaya are given. The work of some other notable geologists in the second half of the 19th C is recorded. This leads to a discussion of isostasy and theories about the structure of this and other mountain chains, including the geosynclinal theory that prevailed up until the end of the 19th C.